(untitled) (Bangladesh Journal of Botany, 2025)
Phenylpropanoids, a class of bioactive compounds found in Lonicera macranthoides Hand.-Mazz, are known for their diverse pharmacological properties. This study focused on the purification of total phenylpropanoids (TP) from Lonicera macranthoides extract (LME) using nine types of macroporous resins. Among them, HPD-100 resin exhibited the highest purification efficiency. Optimal conditions for purification were determined as follows: extract concentration of 10 mg/ml, solution pH of 3, resin dosage of 7 g, elution solution concentration of 60%, elution volume of 30 ml, loading rate of 1.5 ml/min, loading volume of 200 ml, elution rate of 2.0 ml/min, and elution volume of 220 ml. Adsorption kinetics conformed to the pseudo-second-order model, while thermodynamic analysis aligned with the Freundlich isotherm model, indicating spontaneous and exothermic adsorption with negative values for enthalpy, entropy, and Gibbs free energy. Molecular docking further revealed π-π and π-σ interactions between the resin and phenylpropanoid molecules, with a docking score of -3.388 kcal/mol, supporting the resin’s affinity for the target compounds. These findings provide a robust foundation for the efficient extraction and functional evaluation of phenylpropanoids from L. macranthoides. Bangladesh J. Bot. 54(3): 811-821, 2025 (September) Special